2019
DOI: 10.1002/glia.23740
|View full text |Cite
|
Sign up to set email alerts
|

Microglia and sexual differentiation of the developing brain: A focus on extrinsic factors

Abstract: Microglia, the innate immune cells of the brain, have recently been removed from the position of mere sentinels and promoted to the role of active sculptors of developing circuits and cells. Alongside their functions in normal brain development, microglia coordinate sexual differentiation of the brain, a set of processes which vary by region and endpoint like that of microglia function itself. In this review, we highlight the ways microglia are both targets and drivers of brain sexual differentiation. We exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 169 publications
(174 reference statements)
1
45
0
Order By: Relevance
“…In the developing brain, chromosomal sex, gonadal hormone exposure or differential microenvironmental signals might play a role. However, since microglia expression at early postnatal age is very low the most likely mechanism is that prenatal hormone milieu induces differential changes in the microenvironment of males and females and is this different microenvironment the responsible for differences in the activity of microglial activity (VanRyzin, Marquardt et al 2020). For instance, It has been demonstrated that the perinatal surge of testosterone induces an elevated cannabinoid tone in amygdala and this in turn induces a phagocytic ameboid phenotype in male microglia (VanRyzin, Marquardt et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the developing brain, chromosomal sex, gonadal hormone exposure or differential microenvironmental signals might play a role. However, since microglia expression at early postnatal age is very low the most likely mechanism is that prenatal hormone milieu induces differential changes in the microenvironment of males and females and is this different microenvironment the responsible for differences in the activity of microglial activity (VanRyzin, Marquardt et al 2020). For instance, It has been demonstrated that the perinatal surge of testosterone induces an elevated cannabinoid tone in amygdala and this in turn induces a phagocytic ameboid phenotype in male microglia (VanRyzin, Marquardt et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…TLR7 is implicated in miRNA-mediated increased TNFα release, and different expression of Tlr7 in females may contribute to intrinsic differences in immune response [82] . Therefore, male and female microglia are differentially influenced by these factors since early developmental stages [83] .…”
Section: Microglia and Sexual Differentiation Of The Brainmentioning
confidence: 99%
“…Recent work has shown that microglia contribute to sex differences in social behavior [83] and further research will determine to what extent microglia partake in the brain sexual dimorphism. How such intrinsic differences contribute to disease susceptibility also remains to be elucidated [30,39] .…”
Section: Basal Sex Differences In Microglia Functional Responsesmentioning
confidence: 99%
“…For example, in glaucoma, astrocytes have been demonstrated to constitutively perform phagocytosis through internalizations of large portions of axonal cytoplasm and axon-derived organelles [ 85 ]. Interestingly, similarly to microglia [ 86 , 87 ], the phagocytic activity of astrocytes appears to be influenced by sex, as recently demonstrated by the use of synthetic steroids which induce a significantly higher phagocytic activity in astrocytes derived from female mice under resting and inflammatory conditions [ 88 ].…”
Section: Astrocytes Control Synaptic Pruningmentioning
confidence: 99%